Efficacy and safety of intravitreal injection of triamcinolone-moxifloxacin after cataract surgery in a low to middle income country – a one-year audit - Irfan Kabiruddin Jeeva; Masud, Sidra; Muhammad Abdul Rehman Siddiqui (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the safety and efficacy of intravitreal injection of triamcinolone and moxifloxacin regime administered immediately following cataract surgery. Method: The retrospective study was conducted from January to June 2021 at a tertiary care referral centre in Karachi and comprised record of all patients who underwent dropless cataract surgery from April 2018 to June 2019. Data included slit lamp examination, dilated fundal exam, uncorrected visual acuity, best corrected visual acuity, and intraocular pressure. Cataract assessment and anterior chamber reaction were graded according to the World Health Organisation cataract grouping system. Efficacy of the regime was defined as the ability to prevent postoperative endophthalmitis. Stratification analysis was done to note if gender has any role in terms of effectiveness. Data was analysed using Microsoft Excel version 16.0 and IBM SPSS version 27. Results: Of 240 eyes of 161 patients analysed, 114(47.5%) were of men who had a mean age of 57.89±14.32 years, and 126(52.5%) were of females with a mean age of 58.02±10.85 years. Overall, 2(1.75%) male subjects and 1(0.8%) female subject developed breakthrough inflammation within one week of the procedure. They were treated with anti-inflammatory drops and in 1(33%) of the cases antibiotic drop for 1 week. At day 90, no patient had residual inflammation or new onset inflammation. Also, 15(6.25%) patients developed raised intraocular pressure from day 7 to day 30. Most cases 10(66.7%) resolved within 1 week of using intraocular pressure-lowering drops. No patient developed endophthalmitis postoperatively. Conclusion: Dropless cataract regime was found to be an effective and safe alternative that was easy to administer9. Key Words: Dropless cataract surgery, Safety of cataract surgery, Innovations in cataract surgery, Endophthalmitis after dropless.